Education and participation in a new country: Experiences of immigrants, refugees and schools - Ragnarsdóttir, Hanna (Menntavísindasvið Háskóla Íslands, 2020)
Immigration to Iceland has increased rapidly in recent decades. People move to the country for different reasons, some as refugees. Education systems play a vital role in the integration of children and youth to a new society and in supporting their democratic participation. To be able to fulfill these roles, schools must to adjust to the needs of diverse groups of students and develop their practices according to demographic changes. The article, which presents an overview of literature, discusses the experiences of immigrants and refugees in Iceland of education and participation in Icelandic society. The article draws on research conducted with several groups of students at different school levels and their families the last 20 years. The experiences of practitioners in schools, teachers and principals at different levels of the education of children and youth of diverse origins are also addressed, as well as the development of educational practices in the past decades to respond to an increasingly diverse student group. The article concludes with a discussion on possible paths in the education of diverse groups of students in coming years. The theoretical background of most of the research studies is in critical approaches to education (Banks, 2013; May & Sleeter, 2010; Nieto, 2010) where the rights of minority groups to education are emphasized, as well as counteracting inequalities. Nieto (2010) claims that empowerment in schools entails that students are active participants instead of being passive receivers and that teachers build on their students’ resources and abilities in their teaching. The approaches of multilingual education for social justice also form a basis of the article. Scholars (Chumak-Horbatsch, 2012; Cummins, 2004; Skutnabb-Kangas et al., 2009) argue that it is important to make students’ heritage languages visible in schools and build on these in teaching. They note that these basic human rights of every student are often neglected. Theoretical writing on citizenship education, ...